THE NATURE AND TYPES OF DATA - Ahmed, El Hacen Moulaye (PEOPLE: International Journal of Social Sciences, 2019)
The current paper lays out the nature and types of data. It is underpinned by models presented in two chapters from two different books: Walliman’s (2011) “the Nature of Data” and Knight and Parsons’ (2005) “What Kind of Data Do I Need and How Do I Get Them?” The chapters are selected because they represent heuristic and representative models of the nature and types of data. Walliman’s model represented data as a fugacious and fractional sight of the events, opinions, or beliefs. Based on diverse criteria and situations, Walliman governed his typologies. Based on type of source, for example, they were described as either primary or secondary, and based on their characteristics, data can be seen as quantitative or qualitative. Knight and Parsons’ model listed only two categories, primary and secondary. In addition, they explained in depth their advantages and disadvantages which were hesitantly referred to in Walliman’s chapter.